Lipidomics Reveals Common Mechanisms in Polycystic Ovarian Syndrome, Recurrent Spontaneous Abortion, and Infertility: A Genetic-Based Analysis - Tao A; Wu T; Han X; Niu D; Feng X (International Journal of Women's Health)
Ailin Tao,1 Tianqiang Wu,1 Xinyu Han,1 Dingren Niu,1 Xiaoling Feng2 1Department of First Clinical Medical College, Heilongjiang University of Chinese Medicine, Harbin, People’s Republic of China; 2Department of Gynecology, The First Affiliated Hospital of Heilongjiang University of Chinese Medicine, Harbin, People’s Republic of ChinaCorrespondence: Xiaoling Feng, Department of Gynecology, The First Affiliated Hospital of Heilongjiang University of Chinese Medicine, 26 heping Road, Xiangfang District, Harbin, Heilongjiang, 150040, People’s Republic of China, Email doctorfengmen@163.comBackground: Polycystic ovary syndrome (PCOS), infertility, and recurrent spontaneous abortion (RSA) pose significant challenges to women’s reproductive health. While dyslipidemia plays a critical role in these conditions, the causal relationships between specific lipids and these pathologies, as well as their shared mechanisms, remain unclear.Methods: We conducted genome-wide association studies (GWAS) to identify genetic variants associated with 179 plasma lipid species and obtained outcome data for PCOS, infertility, and RSA from the FinnGen R10 database. Mendelian randomization (MR) was performed with genetic variants as instrumental variables (IVs) to assess causal relationships. The inverse variance weighted (IVW) method was the primary approach in our two-sample MR study. Robustness was validated through assessments of heterogeneity, pleiotropy, and leave-one-out analyses.Results: IVW analysis identified 17 plasma lipid species significantly associated with PCOS risk (P < 0.05), including sphingomyelin (d38:2) (OR = 0.909, 95% CI: 0.835– 0.990, P = 0.0277) and triacylglycerol (48:2) (OR = 1.291, 95% CI: 1.097– 1.518, P = 0.0020). Similarly, 15 lipid species were significantly associated with infertility risk (P < 0.05), such as sphingomyelin (d36:2) (OR = 0.926, 95% CI: 0.888– 0.966, P = 0.0003) and triacylglycerol (48:2) (OR = 1.122, 95% CI: 1.059– 1.188, P < 0.0001). Two lipid species, phosphatidylinositol (18:0_20:4) (OR = 0.790, 95% CI: 0.693– 0.900, P = 0.0004) and sphingomyelin (d42:2) (OR = 0.779, 95% CI: 0.672– 0.903, P = 0.0009), showed significant inverse associations with RSA risk, suggesting protective effects.Conclusion: This study establishes causal relationships between specific lipid species and the risk of PCOS, infertility, and RSA, emphasizing lipid metabolism dysregulation as a common pathological mechanism underlying these reproductive disorders. Targeting lipids may offer a promising therapeutic strategy for these diseases.Keywords: polycystic ovarian syndrome, recurrent spontaneous abortion, infertility, lipidomics, Mendelian randomization, causal relationship